2017
DOI: 10.1111/hex.12552
|View full text |Cite
|
Sign up to set email alerts
|

Accessing support and empowerment online: The experiences of individuals with diabetes

Abstract: ContextThe use of the internet for health information by those with long‐term conditions is growing. It has been argued that this represents a form of empowerment by patients, as it enables them to control the content and flow of the information available to them. To explore this, the use of online discussion groups by those with diabetes was examined.MethodSemi‐structured interviews were conducted with 21 participants with type 1 and 2 diabetes and analysed using thematic analysis. Participants were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 59 publications
1
73
0
1
Order By: Relevance
“…Online patient research networks may be able to fill this gap by facilitating connections with patients, rapidly and without geographic bounds, in a space where they are already engaged and activated with others who share their health condition. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Online patient research networks may be able to fill this gap by facilitating connections with patients, rapidly and without geographic bounds, in a space where they are already engaged and activated with others who share their health condition. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Research has alluded to the empowering processes of online communities (Brady et al 2017) and earlier work in this area has pointed towards the increased access to health information that the internet affords, as being likely to bring about such changes in the role and place of formal care in LTC management (Hardy 1999). Patient choice is no longer based solely on the options presented by formal care; with an increasing role being seen for online ties in this context.…”
Section: Discussionmentioning
confidence: 99%
“…First, previous studies have shown that older adults will use online communities to obtain health information related to chronic conditions [6 14]. In order to understand diabetes patients' use of online resources to seek health information, prior studies have frequently employed interviews [46][47][48] and surveys [49 50]. Even in situations where they used content analysis, researchers performed only traditional quantitative content analysis [12].…”
Section: Discussionmentioning
confidence: 99%